(untitled) (Archives of Mechanics - Test, 2000)
We consider two-dimensional thermoelastic composite materials in the case when the temperature is constant. Using complex potentials and applying a method of functional equations, we construct a simple algorithm to solve the corresponding boundary value problem. The stress tensor is written with the accuracy of up to the term O(R2), where R = maxk,m rk dkm-1, rk is the radius of the k-th inclusion, dkm is the distance between centers of the k-th and m-th inclusion (k ≠ m). The effective elastic constants and the coefficient of thermal expansion are written in analytic form up to O(R4).